AN ANALYSIS OF CLEAN SURPLUS VALUATION MODEL IN NIGERIAN LISTED STOCKS (Journal of Global Accounting, 2023)
The study empirically investigates the validity of the clean surplus valuation model in twenty nine selected Nigerian listed stocks. Using a panel co-integration approach, secondary data are collected from the annual reports of selected non-financial firms for the period 2011 to 2017. Analyses include the use of descriptive statistics, panel regression, unit root test and the Hausman test using E-view 8.0 software. Result supports the applicability of the clean surplus model to selected listed Nigerian stock for the period covered. Our result also affirms the assertion that the model is effective for short horizons. We suggest that further researches should introduce other variables to the model to ameliorate the deficiency of having high predictive ability in the short run only. This could improve its ability to predict for longer horizons.
Keywords: Ohlson; Valuation; stock prices; clean surplus; abnormal earnings